Examining the Influence of Food Hygiene on Acute Undernutrition and Its Determinants Among Young Children in Hilly Southern Shan State, Myanmar - Ei Mon Soe; Krittiyanee Thammasarn (International Journal of Public Health Asia Pacific, 2026)
Background: Malnutrition is a major public health concern, disproportionately affecting children in low-resource settings such as Myanmar, where political instability and the COVID-19 economic crisis have exacerbated undernutrition. Objectives: This study aimed to assess the prevalence of acute undernutrition (wasting) and examine the influence of food hygiene practices and other determinants among children under-5 in Southern Shan State, Myanmar. Methods: A cross-sectional study was conducted among 438 caregiver-child pairs in remote villages of Langkho District, Southern Shan State. Data were collected using a structured questionnaire from April to May 2025. Bivariate and multivariable logistic regression analyses were performed. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were reported, with significance set at P < 0.05. Results: The prevalence of wasting was 14.15% (95% CI:11.18-17.75). Wasting was significantly associated with lack of protection of cooked food (AOR=4.84; 95% CI: 2.36-9.91), storage of utensils on open-shelf storage (AOR=2.13; 95% CI: 1.07-4.21), and in random locations (AOR=3.70; 95% CI: 1.39-9.79). Mothers with no formal education had lower odds of wasting (AOR=0.28; 95% CI: 0.12-0.67). Households raising chickens for consumption and sale (AOR=2.93; 95% CI: 1.29-6.59) and pigs (AOR=2.18; 95% CI: 1.09-4.33) had higher odds. Conclusion: Acute undernutrition in rural Southern Shan State is influenced by food hygiene, livestock practices and maternal factors. Integrated interventions addressing food hygiene household livelihoods and maternal support are needed to reduce child wasting.